Algorithms for construction and refinement of unstructured quadrangle meshes on multiconnected domains - Karavaev, Aleksandr Sergeevich; Kopysov, Sergey Petrovich; Ponomarev, Aleksandr Borisovich (Computational Continuum Mechanics, 2012)
An algorithm for constructing non-structured quadrangle meshes (Q-Morph Modification - QMM) is proposed. Modification includes construction of fully quadrangle meshes regardless of the initial number of front edges, construction of domains under different constraints, elaboration of a new procedure for recovering cell convexity, and integration of the approaches for topology and shape optimization of cells. A new version of Schneider's refinement algorithm for unstructured meshes combined with the topological clean-up package of the QMM method is developed.
Keywords: algorithms; numerical methods; mesh construction and refinement; non-structured quadrangle mesh; quality criteria; topological clean-up; program code